Answer:
Step-by-step explanation:
Since the above sequence is a geometric sequence
For an nth term in a geometric sequence
[tex]A(n) = a ({r})^{n - 1} [/tex]
where
a is the first term
r is the common ratio
n is the number of terms
From the question
a = - 6
To find the common ratio divide the next term by the previous term
That's
r = 18/-6 = - 3 or -54/18 = - 3
Since we are finding the 12th term
n = 12
Substitute these values into the above formula
We have
[tex]A(12) = - 6 ({ - 3})^{12 - 1} [/tex]
[tex]A(12) = - 6 ({ - 3})^{11} [/tex]
We have the final answer as
Hope this helps you